2021
DOI: 10.12669/pjms.37.4.4220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of maitland mobilization in patients with Myofascial Chronic Neck Pain: A randomized controlled trial

Abstract: Background and Objective: Myofascial neck pain is a common musculoskeletal problem caused by presence of trigger points and local and referred pain patterns. Chronic neck pain is responsible for the involvement of joints, ligaments, fascia and connective tissue as well. The objective of this study was to assess the effect of Maitland mobilization in patients with myofascial chronic neck pain. Methods: In this randomized, placebo treatment-controlled trial, 30 patients consecutively aged 25-45 years meeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Grade V, called manipulation, is applied with high velocity and low amplitüde. The Maitland technique is also a stretching technique that plays an important role in protecting the patient from muscle spasms (Hengeveld & Banks, 2013; Shabbir et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Grade V, called manipulation, is applied with high velocity and low amplitüde. The Maitland technique is also a stretching technique that plays an important role in protecting the patient from muscle spasms (Hengeveld & Banks, 2013; Shabbir et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…According to the fascia theory, the proximal posterior fascia chain is made up of the deep fascia of the neck and the fascia sheath of the eye. Therefore, when the fascia is damaged, it can cause discomfort in the corresponding areas [ 35 , 36 ]. Additionally, neck pain and other issues may result from irritation of joints, ligaments, fascia, and other tissues.…”
Section: Overview and Application Of The Novel Physical Therapy Techn...mentioning
confidence: 99%
“…Musculoskeletal pain refers to the pain that occurs in bones, muscles, tendons, joints, etc., and may be caused by a variety of neurological, orthopedic and other conditions. 1 Among them, low back pain (LBP) is considered the leading cause of limited mobility worldwide. 2 It is reported that the global point prevalence of LBP is 9.4% and is increasing with age.…”
Section: Introductionmentioning
confidence: 99%